2017
DOI: 10.1016/j.jenvp.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of pro-environmental self-identity on pro-environmental intentions and behaviour: A multi-behaviour study

Abstract: Self-identity is considered as a useful additional predictor in the theory of planned behaviour (TPB).\ud However, previous research generally assessed the impact of pro-environmental self-identity in relation\ud to single behaviours and no studies considered its potential role in moderating the impact of other\ud predictors on behaviour. The present research used a within-persons approach to examine effects across\ud behaviours and a longitudinal design to assess the moderating role of self-identity in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 56 publications
14
122
2
6
Order By: Relevance
“…Finally, future research targeting WI could analyse the role both of healthy eating self-identity, since people tend to be more likely to act, maintain and change behaviours which are in line with the beliefs they have about themselves (Carfora, Caso, Sparks & Conner, 2017).…”
Section: Future Directions and Practical Implicationsmentioning
confidence: 99%
“…Finally, future research targeting WI could analyse the role both of healthy eating self-identity, since people tend to be more likely to act, maintain and change behaviours which are in line with the beliefs they have about themselves (Carfora, Caso, Sparks & Conner, 2017).…”
Section: Future Directions and Practical Implicationsmentioning
confidence: 99%
“…Similar approaches have been taken in relation to exploring health cognition-intention-action effects across behaviors (e.g., Carfora et al, 2017;Conner et al, 2015) or the stress-eating relationship across days (O'Connor et al, 2008). Table 1 reports the means and standard deviations for measured variables for protection and risk behaviors.…”
Section: Analysesmentioning
confidence: 99%
“…Much scholarship has examined the relationship of individual identities to environmental beliefs or actions (Sparks and Shepherd, 1992;Sparks et al, 1995;Whitmarsh and O'Neill, 2010;Carfora et al, 2017)-finding that social identity is quite important to these beliefs and actions in a general sense, as well as to those specifically around climate change (Unsworth and Fielding, 2014). In the United States, for instance, researchers have shown that women tend to care about climate change more than men (McCright, 2010), that white men tend to be the least concerned (McCright and Dunlap, 2011), that partisan identification has a large impact (Davidson and Haan, 2012).…”
Section: Identity and Environmental Practices And Ideologiesmentioning
confidence: 99%